Impact and Bending Tests of Coconut Palm and Thorny Bamboo Laminated Beams for Wooden Ship Keel Construction - Firza Ikramullah; Ferri Safriwardy; Suryadi Suryadi; Reza Putra; Faisal Faisal; Masrullita Masrullita (Electronic Journal of Education, Social Economics and Technology, 2025)
Impact and bending tests were conducted on laminated beams made from coconut palm and thorny bamboo to evaluate their potential as alternative materials for wooden ship keels. The study compared the shock load and bending strength of laminated beams with three-layer variations (3, 5, and 7), arranged in a carvel pattern. Testing followed ASTM D6110-10 for impact and ASTM D143 for bending, with moisture content kept below 18% per BKI standards. Results showed that impact strength increased with more layers, from 0.144 J/mm² (3 layers) to 0.248 J/mm² (7 layers). Bending strength also improved, from 14.37 MPa (3 layers) to 38.32 MPa (7 layers). However, the materials fell into Strength Class IV-V under Indonesian Classification Board standards, making them unsuitable as solid wood alternatives for ship keels due to insufficient strength.